Pengaruh Kualitas Informasi Akuntansi Dan Kepatuhan Wajib Pajak Badan Terhadap Penerimaan Pajak - Deddy Kurniawan (Universitas Islam Kadiri, 2020)
Tax revenue from year to year since the enactment of Law Number 28 of 2007 concerning General Provisions and Tax Procedures, has not yet reached the maximum point in tax revenue. Understanding in accounting information and the level of compliance of corporate taxpayers is one of the factors that must be corrected immediately. 2 (two) criteria that can support the achievement of revenue targets, namely the Quality of Accounting Information and Compliance of Corporate Taxpayers. The research in this thesis aims to: (1) To simultaneously analyze the effect of the quality of accounting information and corporate taxpayer compliance on tax revenue, (2) To analyze the effect of the quality of accounting information on tax revenue, (3) To analyze the effect of Corporate Taxpayer compliance on tax revenue. The research in this thesis uses quantitative analysis methods using numerical data. While the data analysis technique uses: (1) validity and reliability tests, (2) classic-normality assumption test, (3) multiple regression assumption test. The results show that: (1) Quality of Accounting Information and Compliance of Corporate Taxpayers simultaneously affect Tax Revenue, (2) the quality of accounting information effect on tax revenue, (3) corporate taxpayer compliance effect on tax revenue